Composite structure containing translucent layer with UV protective properties
By using a thin film layer made of thermoplastic elastomer and a thin paint layer in the composite structure, both containing UV stabilizers, the problem of the lack of UV protective properties of highly translucent composite structures in the prior art is solved and high light transmittance is achieved and good UV protection.
Patent Information
- Application Number
- CN202380046109.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-15
- Filing Date
- 2023-07-31
- Publication Date
- 2025-01-21
AI Technical Summary
The highly translucent composite structure disclosed in the prior art does not have UV protection properties.
By using a film layer made of a thermoplastic elastomer in a composite structure and a thin paint layer coating the film layer, both containing UV stabilizers, the structure is designed to maintain high light transmittance while allowing visual perception of large-volume additives.
It is possible to provide a high concentration of UV stabilizer while maintaining high light transmittance, giving the composite structure good UV protection properties, while also having a decorative effect and being a coating material suitable for vehicle interiors.
Abstract
Description
Technical Field
[0001] The invention relates to a composite structure comprising a film layer made of a thermoplastic elastomer and a thin paint layer coating the film layer, wherein both the film layer and the paint layer are translucent and contain a UV stabilizer. Background Art
[0002] The prior art discloses coating materials for vehicle interiors. JP 2009-066967 A discloses a translucent sheet material comprising a protective layer and a thermoplastic resin layer, wherein each layer contains a UV stabilizer, and is laminated on a substrate containing a pigment. EP 3 666 518 A1 discloses a composite structure comprising a carrier layer, a foamed cover layer containing a visible lignocellulose-based component, and a lacquer layer coating the foamed cover layer. EP 3 051 023 A1 discloses a composite structure comprising a first layer containing visible cork particles, a second layer, and a lacquer layer coating the second layer and containing a UV stabilizer.
[0003] Problems to be solved by the present invention
[0004] The highly translucent composite structures disclosed in the prior art do not have UV protective properties. Therefore, the problem underlying the present invention is to provide a translucent structure having UV protective properties. This problem is solved by thinning the composite structure to maintain its translucent properties and by adding UV stabilizers to impart the desired UV protective properties. Summary of the invention
[0005] The present invention encompasses the following embodiments.
[0006] [1] A composite structure comprising a support layer, a film layer arranged on the support layer, and a paint layer coating the film layer, wherein the film layer is made of a thermoplastic elastomer, has a thickness of 50 to 500 μm, and contains a UV stabilizer, wherein the paint layer is different in composition from the film layer, has a thickness of 3 to 50 μm, and contains a UV stabilizer, wherein the film layer and the paint layer are formed at λ max A semi-transparent structure having a transmittance of at least 60% under max is a wavelength of maximum transmittance in the range of 400 nm to 700 nm, wherein the support layer contains a bulk additive, and the composite structure allows visual perception of the bulk additive through the translucent structure.
[0007] [1-1] The composite structure according to embodiment [1], wherein the content of the thermoplastic elastomer in the film layer is greater than 80% by mass, preferably greater than 90% by mass.
[0008] [1-2] A composite structure according to one of the preceding embodiments, wherein the visual perception is allowed in the absence of an artificial light source.
[0009] [1-3] The composite structure according to one of the preceding embodiments, wherein the visual perception is allowed in the absence of backlight.
[0010] [1-4] A composite structure according to one of the preceding embodiments, wherein the support layer is coated with the film layer.
[0011] [1-5] The composite structure according to one of the preceding embodiments, wherein the support layer is opaque and contains a pigment.
[0012] [1-6] The composite structure according to one of the preceding embodiments, wherein the support layer is translucent.
[0013] [1-7] A composite structure according to one of the aforementioned embodiments, wherein the support layer is translucent and allows visual perception of a bulky additive, the bulky additive being arranged from the surface to the center of the support layer in the thickness direction.
[0014] [1-8] The composite structure according to one of the preceding embodiments, wherein the support layer contains a thermoplastic elastomer.
[0015] [2] A composite structure according to one of the preceding embodiments, wherein the bulky additive has a size determined by sieving of at least 50 μm, preferably at least 100 μm.
[0016] [2-1] The composite structure according to embodiment [2], wherein at least 50% by mass of the bulky additive has a size of at least 50 μm, preferably at least 100 μm.
[0017] [3] A composite structure according to one of the preceding embodiments, wherein the bulky additive is a natural particle or a natural fiber.
[0018] [4] A composite structure according to one of the preceding embodiments, wherein the support layer is made of a polymer.
[0019] [5] The composite structure according to one of the preceding embodiments, wherein the support layer has a thickness of 50 μm to 2 mm.
[0020] [6] The composite structure according to one of the preceding embodiments, wherein the content of the bulky additive in the support layer is 20 to 70 mass %, preferably 30 to 60 mass %.
[0021] [7] A composite structure according to one of the preceding embodiments, wherein the composite structure allows tactile perception of the bulk additive through the translucent structure.
[0022] [8] A composite structure according to one of the preceding embodiments, wherein the content of the UV stabilizer in the film layer and the paint layer is greater than 0.1 mass %, preferably greater than 0.5 mass %, and more preferably greater than 1 mass %.
[0023] [8-1] A composite structure according to one of the preceding embodiments, wherein the film layer has a thickness of less than 300 μm, the paint layer has a thickness of less than 30 μm, and the content of the UV stabilizer in the film layer and the paint layer is greater than 0.5% by mass.
[0024] [9] A composite structure according to one of the preceding embodiments, wherein at least 90% of the particles of the UV stabilizer have a size of less than 5 μm, preferably less than 2 μm.
[0025]
[10] A composite structure according to one of the preceding embodiments, wherein the total content of the thermoplastic elastomer and the UV stabilizer accounts for more than 90% by mass of the film layer.
[0026]
[11] A composite structure according to one of the preceding embodiments, wherein max The optical transmittance is at least 90%.
[0027]
[12] The composite structure according to one of the preceding embodiments, wherein the thermoplastic elastomer has a crystallinity of less than 30%.
[0028]
[13] According to one of the aforementioned embodiments, the composite structure, wherein the surface of the support layer covered by the film layer comprises a structure containing protrusions and / or depressions.
[0029]
[14] A composite structure according to one of the preceding embodiments, wherein a printed structure is sandwiched between the support layer and the film layer.
[0030] [14-1] A composite structure according to embodiment
[14] , wherein the printed structure has a thickness of 1 to 30 μm, preferably 1 to 20 μm, and more preferably 3 to 10 μm.
[0031]
[15] Use of the composite structure according to one of the preceding embodiments as a surface material in a vehicle interior.
[0032] In addition, the present application covers the following aspects.
[0033] [1] A composite structure comprising a film layer and a paint layer coating the film layer, wherein the film layer is made of a thermoplastic elastomer, has a thickness of 50 to 500 μm, and contains a UV stabilizer, wherein the paint layer is different in composition from the film layer, has a thickness of 3 to 50 μm, and contains a UV stabilizer, and wherein the composite structure is max has a transmittance of at least 60%, preferably at least 80%, wherein λ max is the wavelength of maximum transmittance in the range of 400 nm to 700 nm. [1-1] The composite structure according to aspect [1], wherein the content of the thermoplastic elastomer in the film layer is greater than 80% by mass, preferably greater than 90% by mass.
[0034] [2] The composite structure according to aspect [1], wherein the UV stabilizer is selected from ultraviolet absorbers and hindered amine light stabilizers.
[0035] [3] The composite structure according to aspect [1] or [2], wherein the content of the UV stabilizer in the film layer and the paint layer is greater than 0.1 mass%, preferably greater than 0.5 mass%, and more preferably greater than 1 mass%. [3-1] The composite structure according to one of the preceding aspects, wherein the film layer has a thickness of less than 300 μm, the paint layer has a thickness of less than 30 μm, and the content of the UV stabilizer in the film layer and the paint layer is greater than 0.5 mass%.
[0036] [4] A composite structure according to one of the preceding aspects, wherein at least 90% of the particles of the UV stabilizer have a size of less than 5 μm, preferably less than 1 μm.
[0037] [5] The composite structure according to one of the preceding aspects, wherein the total content of the thermoplastic elastomer and the UV stabilizer accounts for more than 90% by mass of the film layer.
[0038] [6] A composite structure according to any one of the preceding aspects, wherein max The optical transmittance is at least 90%.
[0039] [7] A composite structure according to any of the preceding aspects, wherein the thermoplastic elastomer has a crystallinity of less than 30%, preferably less than 10%. [7-1] A composite structure according to any of the preceding aspects, wherein the thermoplastic elastomer has a gel content of 5 to 50%. [7-2] A combination of aspects [7] and [7-1] is preferred. [7-3] A combination of aspects [7-2] and [3-1] is preferred.
[0040] [8] The composite structure according to any one of the preceding aspects, wherein the thermoplastic elastomer is a thermoplastic polyolefin. [8-1] The combination of aspect [8] with any one of aspects [7], [7-1], [7-2] or [7-3] is preferred.
[0041] [9] A composite structure according to any one of the preceding aspects, wherein the content of aromatic rings in the film layer and the paint layer is less than 10% by mass, preferably less than 3% by mass. [9-1] A composite structure according to any one of the preceding aspects, especially according to aspect [1], wherein the content of aromatic rings in the film layer and the paint layer is less than 10% by mass, preferably less than 3% by mass. max The invention relates to a coating composition having a light transmittance of at least 80% under a temperature of 1000 to 2000 °C, wherein the film layer has a thickness of 50 to 300 μm, the content of the thermoplastic elastomer in the film layer is at least 80% by mass and the content of the UV stabilizer is at least 0.5% by mass, at least 90% of the particles of the UV stabilizer have a size of less than 2 μm, the content of aromatic rings in the film layer and the paint layer is less than 5% by mass, and the crystallinity of the thermoplastic elastomer is less than 20%.
[0042]
[10] A composite structure according to one of the preceding aspects, wherein the paint layer is based on polyurethane.
[0043]
[11] The composite structure according to one of the preceding aspects, comprising a support layer, the film layer and the paint layer, wherein the support layer is coated with the film layer.
[0044]
[12] A composite structure according to aspect
[11] , wherein the support layer contains or is made of a polymer and contains an additive such as a natural fiber, wherein the polymer and the additive differ in their optical properties. [12-1] A composite structure according to aspect
[12] , wherein the film layer and the paint layer are selected to allow visual perception of the additive. [12-2] A composite structure according to aspect
[12] or [12-1], wherein the additive, the film layer and the paint layer are selected to allow tactile perception of the additive. [12-3] A composite structure according to aspects
[12] to [12-2], wherein the content of the additive such as a natural fiber in the support layer is 20 to 70% by mass, preferably 30 to 60% by mass.
[0045]
[13] The composite structure according to any one of aspects
[11] to [12-3], wherein the surface of the support layer covered by the film layer comprises a structure including protrusions and / or depressions. [13-1] The composite structure according to aspect
[13] , wherein the protrusions and / or depressions, the film layer and the paint layer are selected to allow tactile perception of the protrusions and / or depressions.
[0046]
[14] The composite structure according to any one of aspects
[11] to [13-1], wherein a printed structure is sandwiched between the support layer and the film layer. [14-1] The composite structure according to aspect
[14] , wherein the printed structure has a thickness of 1 to 30 μm, preferably 1 to 20 μm, and more preferably 3 to 10 μm.
[0047]
[15] Use of the composite structure according to one of the preceding aspects as a surface material in a vehicle interior.
[0048] Advantages of the present invention
[0049] The thin composite structure of the present invention allows the use of high concentrations of UV stabilizers while maintaining high light transmittance. Thus, the composite structure combines the advantageous effects of a highly translucent material and a UV protective material. An advantageous property of the composite structure as a highly translucent material is that the structure covered by the material is visible in daylight. Thus, the composite structure can be used to achieve decorative effects. An advantageous property of the composite structure as a protective material is that both the material itself and the structure covered by the material are protected against UV light. Thus, the composite structure can be advantageously used as a coating material in vehicle interiors. DETAILED DESCRIPTION
[0050] The composite structure of the present invention contains a film layer and a paint layer as described herein. The paint layer coats the film layer. Thus, the two layers are directly bonded to each other without any material, such as an adhesive, disposed between them.
[0051] In this document, unless explicitly stated otherwise, the terms "composite structure", "support layer", "membrane layer" and "paint layer" respectively refer to the "composite structure according to the present invention", the "support layer contained in the composite structure according to the present application", the "membrane layer contained in the composite structure according to the present invention" and the "paint layer contained in the composite structure of the present invention".
[0052] The structure composed of the paint layer and the film layer is highly translucent. In this article, the meaning of the term "translucency" covers the meaning of "transparency". Generally speaking, transparency is a physical property that allows light to pass through a material without scattering. Translucency is a superset of transparency, allowing light to pass through and allowing scattering. In other words, a translucent medium allows light to pass through, while a transparent medium not only allows light to pass through, but also allows images to be formed. Transparent materials appear clear. Generally, in the present invention, the translucent layer is formed by max The opaque layer is defined as having a transmittance of at least 2%, preferably at least 10%, and more preferably at least 60% at λ. max is defined as having a transmittance of less than 2%, where λ maxIt is the wavelength of maximum transmittance in the range of 400nm to 700nm. Since light transmittance values are affected by absorption, scattering, reflection, etc., the exact light transmittance value of the film may vary depending on the type of light source, the composition and thickness of the film. Light transmittance is also different for different wavelength ranges.
[0053] The light transmittance of the structures described in this application (i.e., individual layers or any composite structure) was determined as follows: Equipment: Datacolor, Model 850; Lamp: Xenon lamp. The total transmittance was measured according to the user guide provided by the manufacturer. A white plate (e.g. The white plate is placed at the front aperture plate. The sample to be measured, such as a film or a composite structure, is placed between the sphere opening and the sensor. In the present invention, the light transmittance of the layer structure (such as a film or a composite structure) is in the range of 400 to 700 nm at the wavelength λ of the maximum transmittance of the layer structure. max The light transmittance [%] is defined as 100% × (in the presence of a layer structure at λ max Transmittance value measured at λ) / (transmittance value measured at λ in the absence of layer structure max The light transmittance of the composite structure composed of the film layer and the paint layer means the transmittance of light emitted at a position facing the lower side of the film layer and detected at a position facing the top side of the paint layer.
[0054] As described in detail below, the polymer of the layer, for example the thermoplastic elastomer (TPE) of the film layer, can be appropriately selected to achieve the desired highly translucent properties. By reducing the amount of oil in the polymer composition, the light transmittance of each layer can be further increased. The optical properties of the composite structure are also controlled by the distribution of the UV stabilizer in the polymer. In the present invention, the uniform distribution of the UV stabilizer in the film layer and the paint layer provides high light transmittance at a given UV stabilizer concentration.
[0055] The composite structure contains UV stabilizers and may contain other additives such as pigments, heat stabilizers, flame retardants and compatibilizers in the film layer and / or the paint layer. Generally, low concentrations of additives may be preferred to achieve very high light transmittance. The pigment may be selected from silica, TiO2, CaCO3, Mg (OH)2, carbon black, organic red, organic yellow, phthalocyanine blue, mica, kaolin, clay, coal dust, lignin, talc, BaSO4, Al (OH)3, ZnO and MgO. In order to provide a composite structure with uniform color and high transparency, the pigment is preferably small to reduce light scattering. The particle size of the pigment is preferably less than 10 μm, more preferably less than 1 μm, and even more preferably less than 100 nm. Heat stabilizers help to maintain the properties of polymers at elevated temperatures. Various heat stabilizers may be used, such as metal salts (stabilizing PVC), organometallic compounds, non-metallic organic stabilizers, organic phosphites and epoxy resins. Organic phosphites protect polymers during the manufacturing process. Phenolic antioxidants protect polymers during their service life. Phenolic antioxidants are free radical scavengers that prevent thermal degradation of polymers. Their effectiveness increases when used in combination with phosphites, thioethers, and light stabilizers. Other examples of antioxidants are sterically hindered phenols such as butylated hydroxytoluene (2,6-di-tert-butyl-4-methylphenol, BHT), butylated hydroxyanisole (BHA), tert-butylhydroquinone (TBHQ), and gallic acid esters. In particular, halogenated polymers such as poly(vinyl chloride) (PVC) may require the use of heat stabilizers.
[0056] The composite structure may be defined by its visible side at the top side of the paint layer and its rear side at the underside of the film layer or support layer, respectively.The structure of the underside may be bonded directly or indirectly, for example, via an adhesive layer.
[0057] The composite structure allows visual perception of bulk additives contained in the support layer through a translucent structure formed by a paint layer and a film layer. This means that the components of the properties of the paint layer, the film layer and the support layer are selected so that when observing the top side of the composite structure, i.e. when observing the visible side with the paint layer as the top layer, a person can visually perceive the bulk additive with the naked eye (i.e., without the help of an instrument). When the visible side of the composite structure is exposed to daylight and there is no backlight, the bulk additive can preferably be perceived through the translucent structure. However, illumination of the rear side (backlight) or visible side of the composite structure is not excluded, and may be preferred in some embodiments. Side lighting can be provided by using a light element arranged in the support layer. "Visual perception of bulk additives" means that at least some of the bulk additives can be identified as separate and individual components of the support layer with the naked eye.
[0058] The composite structure may contain structural elements having optical and / or tactile properties and sandwiched between the support layer and the film layer. During the preparation process, the structural elements may be applied to the top surface of the support layer and / or the lower surface of the film layer. The structural elements may be opaque or colored patterns that form graphic designs, images or logos for decorative or indication purposes. For example, the structural elements may be very thin printed structures visible through the composite structure. The printed structure may be thin enough (e.g., 1 to 30 μm) to be excluded or thick enough (e.g., greater than 50 μm) to allow tactile perception through the film layer and the paint layer. Examples of applied patterns are inkjet printing, screen printing, laser printing, or laser etching.
[0059] The UV stabilizers are preferably uniformly distributed in the film layer and the paint layer to maximize their UV protection effect and minimize their adverse effects on light transmittance. The uniform distribution of the UV stabilizer can be achieved by a method comprising the following steps (a) to (e): (a) providing a polymer selected from at least one thermoplastic elastomer; (b) using the polymer to prepare a first composition containing the polymer and a second composition containing the polymer, wherein the first composition and the second composition preferably have the same composition; the first composition and the second composition prepared in step (b) may be composed of the polymer provided in step (a) and optional additives; (c) mixing the first composition with the UV stabilizer to obtain a masterbatch containing 1% to less than 30% by mass of the UV stabilizer; (d) mixing the second composition and the masterbatch to obtain a layer raw material having a UV stabilizer content of 0.1% to 5.0% by mass; and (e) processing the layer raw material to obtain a film layer or a paint layer.
[0060] In step (a), the polymer may contain a thermoplastic elastomer or consist of a thermoplastic elastomer. In step (b), the first composition and the second composition may consist of more than 90% by mass, preferably more than 95% by mass of the polymer provided in step (a) and less than 10% by mass, preferably less than 5% by mass of at least one of the above-mentioned additives. The first composition and the second composition prepared in step (b) can be obtained by splitting the polymer composition to have the same composition. The polymer can be in particulate form, such as granules or pellets. The first composition and the second composition may contain a blend of a particulate polymer and a particulate additive. In step (c), mixing the first composition and a UV stabilizer to obtain a masterbatch can be carried out by mixing the particulate polymer or blend obtained in step (b) with a particulate UV stabilizer to obtain a blend of a particulate polymer, a particulate UV stabilizer and an additive (if present). Alternatively, mixing the first composition and the UV stabilizer to obtain a masterbatch can be carried out by mixing the first composition and the UV stabilizer in molten form and curing the mixture to obtain a masterbatch, the masterbatch containing particles (e.g., granules or pellets) composed of a polymer, a UV stabilizer, and an additive (if present) or consisting of the particles. In step (d), in the case of a film layer, mixing the second composition and the masterbatch to obtain a layer raw material is preferably carried out in an extruder. The second composition and the masterbatch are preferably melted and mixed in an extruder to achieve a uniform distribution of the polymer, the UV stabilizer, and the additive (if present) in the film layer raw material. In step (e), the film layer raw material, preferably present in a molten form in an extruder, is extruded on a carrier in the form of a film and solidified by cooling to obtain a film layer for the composite structure of the present invention.
[0061] The first composition, the second composition and the masterbatch may contain the polymer provided in step (a) in molten form, and the mixing in step (d) may be carried out in an extruder and the processing in step (e) may include extruding and solidifying the film layer raw material; or the processing in step (e) includes knife coating the film layer.
[0062] In the present invention, the terms "comprises", "comprising", "including", and "having" are inclusive and thus specify the presence of the features, steps, layers and / or components, but do not preclude the presence or addition of one or more other features, steps, layers, components and / or groups thereof. Unless specifically marked as an order of execution, the method steps, processes, and operations described herein should not be construed as necessarily requiring them to be performed in the particular order discussed or shown. It should also be understood that additional steps may be employed.
[0063] Whenever it is mentioned in the context of this specification that a separate composition or layer is based on a certain material or is made of a certain material, this should be interpreted as the corresponding material forming the main component of the composition or layer, wherein other components may also be present in small amounts. In an embodiment, the term "based on" a certain material or "made of a certain material" means a content of greater than 50% by mass, preferably 90% by mass, more preferably 95% by mass.
[0064] As used herein, the singular forms "a", "an", and "the" may also be intended to include the plural forms, unless the context clearly indicates otherwise. For example, components are often described in the singular, such as "a" component or "containing a" component. Unless otherwise indicated, such a singular formulation is intended to include more than one of the indicated component.
[0065] The term "and / or" includes any and all combinations of one or more of the associated listed items. Unless expressly stated otherwise, percentages (%) are mass percentages (mass %). Unless otherwise stated, the standards and specifications referred to refer to the latest versions available at the time of filing this application.
[0066] Film
[0067] The composite structure contains a film layer. The film layer has a thickness of 50 μm to 500 μm, preferably 50 μm to 300 μm, and may consist of one layer or at least two layers. Preferably, the film layer consists of a single layer. The film layer consisting of one layer may be dense or foamed. The film layer containing at least two layers may contain a dense layer and a foam layer. In the present invention, the density of the dense film layer or the dense sublayer is higher than 800 kg / m 3 , preferably higher than 850kg / m 3 , and the density of the foam layer or foam sublayer is less than 800kg / m 3 , preferably less than 500kg / m 3 If the film layer comprises at least two sublayers, these sublayers are preferably directly bonded to one another.
[0068] The film layer contains a thermoplastic elastomer (TPE) or consists of a thermoplastic elastomer (TPE). The film layer may contain more than 80% by mass of TPE, preferably 90% by mass of TPE and less than 10% by mass of the total amount of UV stabilizers and optional additives. In addition to the elastomer, the film layer may contain a thermoplastic or thermosetting polymer selected from polyolefins, polyurethanes, polyvinyl chloride or a combination thereof.
[0069] The film layer preferably exhibits elastic properties and / or thermoplastic properties, more preferably both elastic properties and thermoplastic properties. The elastic properties and other physical properties of the film layer, such as melting point and softness, are determined by its elastomer content. In the present invention, the terms "elastomer" and "rubber" are used synonymously. They refer to polymers that exhibit elastic properties and are crosslinked. Their gel content is preferably 1% to 50%, more preferably 2% to 50%, even more preferably 5% to 50%.
[0070] Thermoplastic elastomers (TPEs) are defined as elastomers that exhibit thermoplastic behavior. The term "thermoplastic" denotes a polymer or polymer composition that exhibits thermoplastic properties, in particular thermoreversibility. TPEs exhibit rubber elasticity within the normal use temperature range. TPEs are copolymers or elastomeric alloys, i.e., physical mixtures of polymers consisting of materials having thermoplastic and elastomeric properties. The desired properties can be obtained by varying the mixing ratio. In general, there are the following general types of TPEs (named according to ISO 18064): styrene block copolymers (TPS), thermoplastic polyolefin elastomers (TPO), thermoplastic vulcanizates (TPV), thermoplastic polyurethanes (TPU), thermoplastic copolyesters (TPC), melt-processed rubbers and thermoplastic polyamides (TPA).
[0071] The TPE may belong to one of the general categories or may be a blend of TPEs from two or more of the categories. Moreover, the TPE may be selected from one category and may be one TPE from one category or a blend of two or more TPEs from one category. The content of TPE in the film layer is preferably at least 50%. The total content of thermoplastic polymers in the film layer, i.e. the total amount of TPE and thermoplastic polymers other than TPE, is preferably at least 80%, more preferably at least 90%. Preferably, the total content of polymers in the film layer consists of TPE and thermoplastic polymers other than TPE. More preferably, the total content of polymers in the film layer consists of thermoplastic polymers (i.e. TPE and other thermoplastic polymers such as TPO) and is at least 80%, most preferably at least 90%.
[0072] TPVs as a class of TPEs combine the properties of vulcanized rubber with the processing properties of thermoplastics. TPVs contain rubber particles that are cured by vulcanization. The rubber particles are encapsulated in a thermoplastic matrix.
[0073] The rubber can be selected from natural rubber (NR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), carboxylated nitrile rubber (XNBR), butyl rubber (IIR), chlorinated butyl rubber (CIIR), brominated butyl rubber (BIIR), polychloroprene (CR), styrene-butadiene rubber (SBR), polybutadiene (BR), ethylene-propylene-diene terpolymer (EPDM), ethylene-propylene rubber (EPR or EPM), silicone rubber, acrylic rubber (ACM), ethylene-vinyl acetate copolymer rubber (EVM), polyurethane rubber (PU) and any combination thereof. The rubber can also be a styrene-based thermoplastic elastomer (STPE).
[0074] In particular, the rubber can be selected from ethylene / α-olefin copolymer rubber (EAM) and ethylene / α-olefin / diene terpolymer rubber (EADM). Preferably, the diene in the ethylene-α-olefin-diene rubber is preferably a non-conjugated diene. Suitable non-conjugated dienes include dicyclopentadiene, alkyl dicyclopentadiene, 1,4-pentadiene, 1,4-hexadiene, 1,5-hexadiene, 1,4-heptadiene, 2-methyl-1,5-hexadiene, cyclooctadiene, 1,4-octadiene, 1,7-octadiene, 5-ethylidene-2-norbornene, 5-n-propylene-2-norbornene and 5-(2-methyl-2-butenyl)-2-norbornene. In a preferred embodiment, the rubber component comprises ethylene-α-olefin-diene rubber. The ethylene-α-olefin-diene rubber may comprise an α-olefin having 3 to 8 carbon atoms. The α-olefin in the EAM or EADM rubber is preferably propylene; in this case, the rubber is referred to as EP(D)M. Here, EPM may also be referred to as EPR. Mixtures of the above rubbers may also be used. For example, the rubber consists of EPDM and EPR. In this case, EPDM preferably accounts for at least 80% by mass of the total rubber content in the cover layer.
[0075] EPDM is made of ethylene, propylene and a diene comonomer that can be crosslinked via a sulfur vulcanization system. EPDM contains crosslinking and is preferably fully cured, i.e. crosslinked to at least 98% and most preferably to 100%. The content of propylene is preferably 45% to 85% by mass. Preferred dienes for making EPDM rubber are ethylidene norbornene (ENB), dicyclopentadiene (DCPD) and vinyl norbornene (VNB). EPDM can be mixed with fillers such as carbon black and calcium carbonate and with plasticizers such as paraffin oil.
[0076] EPR (also referred to as "EPM") is a random copolymer of ethylene and propylene. EPR is similar to EPDM, but does not contain diene units. It uses free radical methods such as peroxides for crosslinking. EPRs of different properties can be obtained by changing the monomer ratio. EPR preferably contains 40 to 80% by mass, more preferably 40 to 60% by mass of ethylene units. It is generally known that EPR copolymers containing less than about 40% by mass of ethylene have poor elasticity at low temperatures, and therefore may provide compositions that are too hard and lack a balance of mechanical properties over the wide temperature range required for most automotive applications. Under high levels of ethylene (generally greater than about 60% by mass of ethylene units), separate crystalline ethylene domains can be formed in the rubber component, and interphase adhesion and miscibility are reduced.
[0077] The thermoplastic elastomer may have the shape of particles. The particles are preferably embedded in a matrix of other polymers present in the layer. The particle size is preferably below 10 μm, more preferably below 1 μm. Preferably, at least 90% of the particles have a size less than 10 μm. The size can be determined by scanning electron microscopy (SEM) of a cross section of the layer. The longest diameter of the particle image in the SEM micrograph is defined as its size.
[0078] In TPV, rubber particles are encapsulated in a thermoplastic matrix containing thermoplastic polymers such as thermoplastic polyolefins (TPO) and / or thermoplastic polyvinyl chloride (PVC). This property allows the film layer to be thermally bonded to the underlying layer without the use of adhesives. The thermoplastic nature requires that the overall crosslinking level should not be too high. The gel content is preferably between 0% and 20%.
[0079] TPO is a polymer prepared by chain polymerization from olefins such as ethylene, propylene, 1-butene or isobutylene. It is a semi-crystalline thermoplastic polymer that is easy to process. Examples of TPO are polyethylene (PE), polypropylene (PP), polymethylpentene (PMP), polyisobutylene (PIB) and polybutene (PB, polybutene-1). Polyethylene (PE) is defined herein as a polymer or copolymer with a weight proportion of ethylene greater than 50%. Polypropylene (PP) is defined herein as a polymer or copolymer with a weight proportion of propylene greater than 50%. Examples of TPO are blends of polyethylene (PE) and polypropylene (PP). Examples of PE are HDPE, LDPE and LLDPE. HDPE has a weakly branched polymer chain and therefore has a molecular weight of 0.94 g / cm 3 Up to 0.97g / cm 3LDPE is a thermoplastic made from the monomer ethylene and has a high degree of short and long chain branching, which means that the chains do not form a crystalline structure and LDPE imparts isotropic properties. This results in lower tensile strength. LLDPE is a substantially linear polymer and is prepared by copolymerization of ethylene with longer chain olefins. Examples of such olefins are 1-butene, 1-hexene and 1-octene, which result in short chain branches in the polymer chain. LLDPE contains branches derived from comonomers that are no longer than 1-octene, while LDPE also contains branches derived from longer comonomers. LLDPE has a higher tensile strength than LDPE, and it exhibits higher impact and puncture resistance than LDPE. LLDPE shows toughness, flexibility and relative transparency. LLDPE is less shear sensitive than LDPE due to its narrower molecular weight distribution and shorter chain branching. LLDPE imparts melt strength. The linearity of LLDPE results from the different manufacturing methods of LLDPE and LDPE. Generally, LLDPE is prepared by copolymerization of ethylene and α-olefin at a relatively low temperature and pressure. LLDPE can be advantageous in ensuring excellent plasticity based on appropriate elongation and ensuring rigidity at break at a certain strength level or higher.
[0080] The thermoplastic polymer may be thermoplastic polyvinyl chloride (PVC). The properties of PVC are adjusted by adding plasticizers. The addition of plasticizers imparts plasticity such as yield and softness to the polymer. Plasticizers include phthalates, chlorinated paraffins, adipates, phosphates, acetyl tributyl citrate, and diisononyl 1,2-cyclohexanedicarboxylate. PVC may contain up to 40% plasticizer. PVC may be mixed with additives to improve its physical properties, such as toughness and elasticity, and to improve processability. Examples of such additives are stabilizers and impact modifiers. For example, PVC without plasticizer may have an elongation at break / tensile strength at break of 10 to 50%, while PVC may have an elongation at break / tensile strength at break of 170 to 400%, depending on the structure and amount of the plasticizer.
[0081] The example of the blend of rubber and TPO is the blend of EPDM and PE and / or PP, EPM and PP and / or PE and ethylene propylene blend, and SEBS and TPO such as the blend of PE and / or PP. The composition can contain such an elastomer such as EPR or EPDM or SEBS, and has such a degree of crosslinking that the composition is still thermoplastic. For example, the resin component can be composed of 10 to 90 parts by weight of polyolefin resin and corresponding 90 to 10 parts by weight, preferably 10-80 / 80-20 parts by weight, more preferably 30-70 / 70-30 parts by weight of rubber. TPV based on polypropylene (PP) and EPDM rubber can be preferred.
[0082] In addition to UV stabilizers, the film layer may contain conventional additives such as plasticizers, stabilizers, anti-aging agents (e.g., antioxidants), fillers and pigments (silicon dioxide, TiO2, CaCO3, Mg(OH)2, carbon black, mica, kaolin, clay, coal dust, lignin, talc, BaSO4, Al(OH)3, ZnO and MgO), flame retardants (e.g., antimony trioxide or zinc hydroxystannate), waxes, colorants, compatibilizers and other auxiliary substances (e.g., viscosity aids, adhesion promoters, etc.). However, the content of these additives may be limited due to the requirement for high translucency of the composite structure.
[0083] The film layer and the TPE contained therein must be highly translucent. The optical properties of polymers are determined by their structure. Generally, amorphous polymers provide transparency, while crystalline polymers provide opacity, especially in thicker products such as injection molded final products. Crystallinity reduces transparency by causing refraction and reflection of light and light scattering at the boundary between crystalline and amorphous regions. The light transmittance of semi-crystalline polymers can be improved by additive technology. Polypropylene injection molded products can be made clearer by adding clarifiers. Very low density polyethylene made with metallocene catalysts will also show improved clarity due to reduced crystallinity. Polypropylene provides high clarity due to its slower crystal growth. Since polyethylene crystallizes very quickly, clarifiers will not improve the clarity of polyethylene products even at a smaller thickness. The crystal structure is usually very ordered and therefore strong and rigid. Typical polymers are "semi-crystalline" with a crystallinity of 10% and 80%. Examples of semi-crystalline polymers are linear polyethylene (PE) or isotactic polypropylene (PP). Amorphous polymers are flexible and elastic because their random molecular structure allows chains to cross each other. On the other hand, amorphous polymers are characterized by relatively low heat resistance, toughness at low temperatures and low dimensional stability. Therefore, it may be preferred that the polymer is not too amorphous and has a certain degree of crystallinity. In the present invention, the degree of crystallinity can be adjusted to achieve the desired balance of optical properties and other physical properties such as flexibility. In the present invention, the degree of crystallinity can be adjusted to achieve the desired balance of optical properties and other physical properties (such as flexibility). In particular, the addition of rubber components can reduce the degree of crystallinity.
[0084] The polymer contained in the film layer is preferably resistant to UV radiation. Since polymers with UV absorbing groups, such as aromatic rings, are sensitive to UV degradation, the TPE in the film layer preferably contains a very low concentration of aromatic rings, such as less than 5 wt%, preferably less than 1 wt%, more preferably less than 0.1 wt% and most preferably 0 wt%. In other words, the polymer is preferably non-aromatic.
[0085] paint layer
[0086] The film layer is coated with a paint layer, which is the uppermost layer of the composite structure. The paint can be a conventional material. The thickness of the paint layer is 3 to 50 μm, more preferably 3 to 10 μm. The paint layer is applied directly to the film layer as a finish for the composite structure and a defense against chemical agents, physical damage (such as scratches or abrasions) and UV radiation. The paint layer can further reduce surface adhesion. Conventional paints for artificial leathers for vehicle interiors can be used, such as paint layers based on silicone-containing aliphatic polyurethanes. The paint layer is generally composed of one or more, preferably up to four transparent paint layers. The paint layer is preferably elastic. The properties of the paint layer, such as elasticity and translucency, can be adjusted to correspond to the corresponding properties of the film layer.
[0087] The polymer contained in the film layer is preferably resistant to UV radiation. For this reason, the polymer in the paint layer preferably contains a very low concentration of aromatic rings, for example less than 5% by weight, preferably less than 1% by weight, more preferably less than 0.1% by weight and most preferably 0% by weight. In other words, the polymer is preferably non-aromatic.
[0088] UV Stabilizers
[0089] The composite structure contains a UV stabilizer as an additive to achieve the purpose of maintaining the desired light transmittance after exposure to UV radiation. The UV radiation range is between 280 and 400 nm wavelength. Polymers are sensitive to UV radiation of certain wavelengths. For example, polypropylene has three maxima at 290 to 300, 330 and 370 nm, and PVC homopolymer has a maximum at 320 nm. Other examples of UV sensitive polymers are polyethylene (300 to 310 nm, 340 nm), PVC copolymers (330 nm, 370 nm) and polyurethane (aromatic) (350 to 415 nm). Suitable UV stabilizers can be ultraviolet light absorbers and hindered amine light stabilizers (HALS). Rutile titanium oxide is effective in the range of 300 to 400 nm, but is not very useful in the very short wavelength UVB range of less than 315 nm. Hydroxybenzophenone and hydroxyphenylbenzotriazole have the advantage of being particularly suitable for transparent applications. Other UV absorbers include oxalanilides for polyamides, benzophenones for PVC, and benzotriazoles and hydroxyphenyltriazines. Hindered amine light stabilizers (HALS) share a 2,2,6,6-tetramethylpiperidine ring structure. HALS are particularly effective in polyolefins and polyurethanes. Any of these compounds can be combined. Some of these combinations have synergistic effects. For example, benzotriazoles are often combined with HALS.
[0090] The UV stabilizer may be in particulate form, such as powder and / or granular form, and may have a size of 0.01 μm to 10 μm, preferably 0.01 μm to 1 μm, more preferably 0.01 μm to 0.1 μm. Smaller sized particulate forms may be preferred to avoid or reduce light scattering. For this reason, a size of less than 400 nm may be preferred.
[0091] Support layer
[0092] The support layer is arranged on the lower side of the membrane layer. Preferably, the support layer is coated with the membrane layer, so it is in direct contact with it. The thickness of the support layer is preferably 0.1 to 3.0 mm, more preferably 0.3 to 2.0 mm. The support layer can be a flexible and / or soft or rigid and / or hard material. In one embodiment, the support layer is transparent, flexible and soft. Due to high concentrations of pigments and / or bulky additives, the support layer can be opaque. In this case, only those bulky additives exposed to the surface of the support layer or disposed near the surface of the support layer can be visible. The support layer can be transparent or translucent, in which case the bulky additives can be visible on the entire or almost the entire support layer in its thickness direction. In this case, an additional opaque layer can be arranged at the lower side of the support layer. The support layer can be made of any material, and is preferably made of polymers such as polyolefins, polyurethanes or polyvinyl chloride. A thermoplastic elastomer can be included to impart elasticity. The support layer can be a dense layer or a foam layer. The support layer contains additives that are different from the polymers in the support layer in their optical properties. Such additives can be color pigments. The support layer contains a bulky additive, i.e., a bulky component. Bulk means that the size (particularly length and width) of the additive makes visual perception possible. For this reason, the additive has a size of at least 20 μm, preferably at least 50 μm, more preferably at least 100 μm. The size can be determined by screening and a bulky additive can be selected. The fiber size of at least 50 μm determined by screening means that the maximum diameter of the fiber is at least 50 μm. The bulky additive can have any shape, such as the shape of a sphere, particle, fiber or disc, and can be a natural or synthetic product. The fiber is defined as having a length of at least 10, preferably at least 20, more preferably at least 50 to a ratio of the maximum diameter. The particle is defined as having an aspect ratio preferably less than 5, more preferably less than 2, i.e., the ratio of the maximum diameter to the minimum diameter orthogonal thereto. The particle can have a spherical or elliptical shape.
[0093] An example of the bulky additive is a lignocellulose-based component (LBC). LBC can be a fiber or a particle. The maximum dimension, i.e., the length of the fiber or the maximum diameter of the particle, can be in the range of 100 to 3000 μm, preferably 100 to 1000 μm. In one embodiment, the length of the fiber is 200 to 600 μm, wherein the fibers in the range account for at least 90% by weight of all LBC in the support layer. LBC is a natural lignocellulose-containing polymer derived from plants. LBC contains lignin and cellulose and optionally hemicellulose. LBC can be a natural fiber and can be derived from plants. Plants that produce cellulose fibers can be divided into bast fibers (jute, flax, ramie, hemp and kenaf), seed fibers (cotton, coconut shell fiber and kapok), leaf fibers (sisal, pineapple and abaca), grass and reed fibers (rice, corn and wheat) and core fibers (hemp, kenaf and jute) and all other species (wood and roots). Fibers from oil palm, sisal, flax and jute are typical examples. The bulky additive can be a particle. In this case, the support layer preferably has a thickness greater than the particle size. The LBC particles may be cork particles. The cork particles may be dried and / or decomposed before use. Suitable cork particles and methods for their preparation are described in EP 3 051 023 A1. Preferably, at least 90% by volume of the cork particles contained in the support layer have a diameter of 10 μm to 500 μm, more preferably 10 μm to 200 μm. Pretreatment may be used to modify the LBC to reduce the hydrophilicity of the LBC to enhance its chemical affinity for and compatibility with the polymer matrix. Lightweight LBC may be used to reduce the density of the support layer. The density of the LBC is preferably less than 500 kg / m 3 , more preferably less than 300kg / m 3 The support layer may be a foamed layer comprising polyvinyl chloride, LBC and hollow microspheres, as described in EP 3 666 518 A1.
[0094] The addition of the bulky components may result in their tactile perception at the surface of the support layer. Tactile perception means that a human user can feel the structure by the touch of his fingers. The structure and size of the bulky components and the light transmittance, color and thickness of the composite structure may be appropriately selected so that visual and / or tactile perception of the bulky components and therefore of the support layer is possible or impossible. The support layer may have protrusions and / or depressions of such size on its top side surface that tactile perception is possible. Since the film layers and paint layers of the composite structure are very thin, for example having a total thickness of less than 300 μm, they do not adversely affect the optical and / or tactile properties of the structural elements of the support layer.
Claims
1. A composite structure comprising a support layer, a film layer arranged on the support layer, and a paint layer coating the film layer, wherein the film layer is made of a thermoplastic elastomer, has a thickness of 50 to 500 μm, and contains a UV stabilizer, wherein the paint layer is different in composition from the film layer, has a thickness of 3 to 50 μm, and contains a UV stabilizer, wherein the film layer and the paint layer are formed at λ max A semi-transparent structure having a transmittance of at least 60% under max is a wavelength of maximum transmittance in the range of 400 nm to 700 nm, and wherein the support layer contains a bulk additive, and the composite structure allows visual perception of the bulk additive through the translucent structure. 2 . The composite structure of claim 1 , wherein the bulky additive has a size of at least 50 μm.
3. A composite structure according to any one of the preceding claims, wherein the bulky additive is a natural particle or a natural fiber.
4. A composite structure according to any of the preceding claims, wherein the support layer is made of a polymer. 5 . The composite structure according to claim 1 , wherein the support layer has a thickness of 50 μm to 2 mm.
6. The composite structure according to any of the preceding claims, wherein the content of the bulky additive in the support layer is 20 to 70% by mass.
7. The composite structure according to any of the preceding claims, wherein the composite structure allows tactile perception of the bulky additive through the translucent structure.
8. The composite structure according to any one of the preceding claims, wherein the content of the UV stabilizer in the film layer and the paint layer is greater than 0.1% by mass.
9. The composite structure according to any of the preceding claims, wherein at least 90% of the particles of the UV stabilizer have a size of less than 5 μm.
10. The composite structure according to any of the preceding claims, wherein the total content of the thermoplastic elastomer and the UV stabilizer is greater than 90% by mass of the film layer.
11. A composite structure according to any one of the preceding claims, wherein max The optical transmittance is at least 90%.
12. A composite structure according to any one of the preceding claims, wherein the thermoplastic elastomer has a crystallinity of less than 30%.
13. The composite structure according to any of the preceding claims, wherein the surface of the support layer covered by the film layer comprises a structure comprising protrusions and / or depressions.
14. A composite structure according to any one of the preceding claims, wherein a printed structure is sandwiched between the support layer and the membrane layer.
15. Use of a composite structure according to one of the preceding claims as a surface material in a vehicle interior.
Citation Information
Patent Citations
Film containing cork particles , artificial leather containing cork particles and method for producing the same
EP3051023A1
Transparent, weather-resistant barrier film having an improved barrier effect and scratch resistance properties
CN103003062A
Decorative sheet
JP2009066967A
Clear coat / color coat finish containing an ultraviolet light stabilizer
WO1981000233A1